CHRONIC PHARYNGITIS: ETIOLOGY, PATHOGENESIS, TREATMENT. NEW APPROACHES TO THE ESTIMATION OF ETIOPATOGENESIS - A. V. Gostry; A. V. Simonova; N. A. Mikhailova; I. A. Snimshchikova; G. A. Osipov; B. V. Agafonov; V. I. Egorov; V. V. Pchelyakova; R. V. Gorenkov; S. Yu. Chudakov; A. A. Karabinenko; N. N. Shevtsova; et al. (Архивъ внутренней медицины, 2019)
The work discusses modern issues of etiopathogenesis, treatment of chronic pharyngitis. The results of the application of a modern method for the diagnosis of mass spectrometry of microbial markers (MSMM), which allows to detect the microorganisms in a biofilm, in a “sleeping state” under the protection of mucin are presented. With the help of this express method, it is possible to conduct a determination of the content in a smear from the pharynx 57 biomarkers of microorganisms at the same time 2 hours after delivery to the laboratory. It was found that 100% of the examined patients with a recurring course of HF (n = 62) increased the total content of microorganisms, which indicates the need for antibacterial therapy; 87% of patients have elevated levels of endotoxin, which is a sign of general intoxication; 71% of patients have reduced plasmalogene content and these patients may be at increased risk for lipid metabolic disturbances; in 100% of the examined patients with frequent exacerbations of CP in the pharynx the nasopharyngeal microflora (coccal) is determined, as well as new etiopathogenetically significant microorganisms (not detected by PCR and cultures), among which there are 7 transient microorganisms (normally in the orifice their level = 0), 11 resident (6- found in the throat in the norm in the minimum level and 5 in the high content). Also, with the help of MSMM, a significant or moderate increase in the content of herpes, cytomegalovirus was detected in the majority (75%) of patients, which indicates the important role of the viruses of the herpes group in the etiopathogenesis in the recurrent course of CP; level of Candida spp. elevated in half of patients; the content of normal microflora is increased in 71% of patients, which indicates the preservation of local resistance in patients with chronic HF, examined by the authors. Thus, the use of MSMM for chronic fever allows to identify new etiopathogenetic microorganisms, on this basis to prescribe a more effective therapy. Thus? it is possible to carry out personified, more effective treatment.